Clinical researchA meta-analysis of the benefit of probiotics in maintaining remission of human ulcerative colitis: evidence for prevention of disease relapse and maintenance of remission - Rahimi, Roja; Nikfar, Shekoufeh; Rezaie, Ali; Abdollahi, Mohammad (Archives of Medical Science, 2008)
Introduction: Probiotics are living microorganisms that, upon ingestion in specific numbers, exert health benefits beyond those of basic nutrition. They are used for preventing relapse of ulcerative colitis but there is not enough evidence to prove their effectiveness. The aim of the study was to evaluate the efficacy of probiotics in preventing relapse of ulcerative colitis and compare their efficacy with mesalazine as a standard treatment for ulcerative colitis. Material and methods: PubMed, Embase, and Cochrane Central Register of Controlled Trials were searched for studies investigating the efficacy of probiotics in maintaining remission of ulcerative colitis. Relapse rate was the key outcome of interest. Data were searched within the time period of 1966 to January 2008. Results: Two controlled trials which determined the efficacy of probiotics and 4 which compared the efficacy of probiotics with mesalazine in preventing relapse of ulcerative colitis met our criteria and were included in the meta-analysis. Pooling of 2 trials for the efficacy of probiotics yielded a significant odds ratio of 0.0269 [95% confidence interval (CI) 0.0049-0.1478, P<0.0001). The odds ratio for 4 studies which compared the efficacy of probiotics with mesalazine was 0.99 (95% CI 0.67-1.48, P=0.9419), a non-significant odds ratio. Conclusions: Probiotics are effective in maintaining remission and their effect in preventing relapse is comparable with mesalazine.